PENGGUNAAN MEDIA PEMBELAJARAN POWERPOINT UNTUK MENUNJANG KONSENTRASI BELAJAR SISWA PADA PEMBELAJARAN IPAS DI SD 56/1 KELAS III DESA ARO - Shelfi Maydini; Anisa Saryanti; Kristina Oktavia s; Tias Nuraini; Khoirunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the extent to which the use of learning media can improve the concentration and learning activeness of third-grade students at SDN 56/1 Desa Aro in the IPAS subject. The problem identified was that students often lost focus and were less active during lessons due to the teacher's one-way or lecture-based teaching method. The research was conducted through observation, interviews, and documentation involving the teacher and 16 students. The results showed that before using varied learning media, students often lost attention and were unfocused during the learning process. However, after the teacher began using media such as PowerPoint presentations with images, videos, and animation features, students became more focused, engaged, and enthusiastic about learning. This media helped students better understand concrete materials, such as.